(untitled) (Bioresearch Communications, 2022)
Recent scientific advancements have sparked an increasing trend of returning to nature. Scientists worldwide prefer natural medical derivatives over synthetic ones due to fewer side effects. Green tea is abundant in bioactive components and vitamins. Although most components of green tea were thought to be absorbed inadequately by oral administration, they are essential for better health. In the present study, an in silico approach was taken to evaluate the effect or correlation of bioactive components of tea on memory retention, cognitive performance, and prevention of neurodegenerative diseases that result in memory alterations, dementia, and cognitive dysfunction. Furthermore, binding of bioactive components with brain-specific proteins and possible alterations in those proteins due to tea components were illustrated. Four critical brain-specific proteins were evaluated in the present molecular analysis. Cyclooxygenase 1 (COX1), Acetylcholinesterase (AChE), Amyloid-β Precursor Protein (APP1), and Cytochrome P4502D6 (Cyp2D6) were the proteins involved. Their interaction with the bioactive components of green tea was evaluated using computational molecular docking analysis (CMDA). The bioactive molecules were Epigallocatechin gallate (EGCG), L-Theanine, Kaemferol, Coumarin, and Myricetin. The beneficial effect of green tea on memory was prioritized in this study. CMDA has shown possible inhibition of acetylcholinesterase, amyloid-β protein, cyclooxygenase 1, and Cytochrome P4502D6 (Cyp2D6). Bioactive components of green tea passed the blood-brain barrier and influenced short-term memory at low concentrations. Significant dosage or concentration in capsulated form might result in long-term effects since both bioavailability, and concentration of essential components of green tea are scarce. Bioresearch Commu. 8(2): 1113-1123, 2022 (July)